2014
DOI: 10.5897/ajb2014.14122
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth and nutrient uptake in response to foliar application of sodium and calcium chloride in cowpea cultivars (Vigna unguiculata L. Walp)

Abstract: In this stu unguiculata Three treatm and CaCl 2 w resulted in PG and Tsa significantly contents d changes w tolerance i through the osmotic ad contributing the analysi cultivars w cultivated parameters develop on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, when unsaturated, 1% manure BC also increased Na. Taffouo et al [ 43 ] reported that root, stem, and leaf dry weight yields decreased in several V. unguiculata cultivars with increasing NaCl concentration. This negative effect was also observed in our study, where Na soil content was negatively correlated with V. unguiculata herbage (r = −0.64; Table 10 ) and root dry weight (r = −0.48; Table 10 ) yields.…”
Section: Discussionmentioning
confidence: 99%
“…However, when unsaturated, 1% manure BC also increased Na. Taffouo et al [ 43 ] reported that root, stem, and leaf dry weight yields decreased in several V. unguiculata cultivars with increasing NaCl concentration. This negative effect was also observed in our study, where Na soil content was negatively correlated with V. unguiculata herbage (r = −0.64; Table 10 ) and root dry weight (r = −0.48; Table 10 ) yields.…”
Section: Discussionmentioning
confidence: 99%